PEMANFAATAN LAHAN DI BAWAH POHON KELAPA DENGAN POLA TANAM TUMPANGSARI DI DESA POIGAR KECAMATAN SINONSAYANG - Diana Meheda; Esry H. Laoh; Ellen G. Tangkere; Jean F.J. Timban (Universitas Sam Ratulangi, 2015)
ABSTRACTThe objective of this research is to determine whether intercropping planting patterns affect the level of coconut production and income of coconut’s farmers and which cropping patterns intercropping will result in bigger production and coconuts’farmer incomeThe research result showed that intercropping cropping patterns provide different levels of coconut production. Cropping patterns that affects most large coconut production was coconut-corn cropping pattern. Intercropping cropping patterns affected the income of farmers. Cropping pattern that gives the biggest farmer's income was coconut-rice cropping pattern.